Neurocognitive And Psychiatric Assessment Following Recovery From Acute Organophosphate Poisoning (International Journal of Environmental Sciences, 2025)
Background: Organophosphate (OP) exposure can have long-term consequences, including cognitive abnormalities. The purpose of this study was to evaluate if acute OP poisoning was related with neurocognitive and/or mental sequelae following clinical recovery from the acute cholinergic phase, using follow-up examination. Methods: This prospective cohort research included 32 patients (group 1), both sexes, aged 18 to 60 years old, who had acute OP poisoning. Healthy volunteers (group 2) were also included, who were matching in age and sex to group 1. Results: Regarding neurocognitive and psychiatric assessment, there was significant improvement after 3 months compared to that on discharge and 6 weeks. There was a significant positive correlation between Rapid emergency medicine score (REMS) and Hamilton anxiety scale on discharge and after 6 weeks and (REMS and Hamilton depression scale on discharge).Conclusions: Acute OP poisoning is related with poor memory, planning, and attention, which can exist beyond clinical recovery and appear to improve after three months. Acute OP poisoning may have psychological consequences such as anxiety and depression, which appear to be reversible.